Study of indium tin oxide–MoS2 interface by atom probe tomography - Ramos Murillo, Manuel Antonio (2019)
The molybdenum disulfide (MoS2) and indium tin oxide (ITO) interface were studied by atom probe tomography (APT). Raman spectroscopy, scanning electron microscopy, and grazingincidence x-ray diffraction measurements were performed as complementary characterization. Results confirm that nanowires plated shape with the 〈110〉-orientation are aligned perpendicular to the ITO film with principal reflections at (002), (100), (101), (201), and Raman spectroscopy vibrational modes at E 2g at 378 cm and A1g at 407 cm correspond to 2H-MoS2. APT reveals MoS , MoS as predominant evaporated molecular ions on the sample, indicating no significant diffusion/segregation of Mo or S species within the ITO layer.